Knowledge Management Implementation Inthe Malaysian Telecommunication Industry: An Empirical Evaluation - Chong, Chin Wei (2007)
The objectives of this study are to assess the readiness and overall perception of telecommunication organisations towards KM implementation; develop valid measures f variables, i.e. preliminary success factors, strategies and processes; compare the differences between perceived importance and the actual implementation of KM elements; examine the associations of KM elements with KM process effectiveness and organisational performance; and analyse the interactions between organisational demographic characteristics and the KM elements with KM process effectiveness and organisational performance.